Thermal desorption of HCH: Temperature and time effects - Araújo, M. M.; Ignatius, S. G.; Oliveira, A. O.; Oliveira, S. S.; Fertonani, F. L. [UNESP]; Paste, I. A. [UNESP] (Springer Nature, 2016)
To evaluate the effectiveness of the thermal remediation of soil decontamination, samples containing organochlorine insecticide hexachlorocyclohexane (HCH) were subjected to different temperatures depending on the exposure time. For this study, reference material and technical grade HCH were heated separately at β = 1 and 10°C min-1 in a thermogravimetric analyzer and contaminated soil samples were heated in an oven at different temperatures and heating time. To determine gaseous emissions generated during the heating of HCH isomers, HCH technical grade samples were heated in a closed system (reactor) and sample gases/vapors were collected for qualitative analysis. The results indicate that the contaminants are removed from soil to temperatures considerably lower than the respective boiling point. The thermogravimetric curves have shown that heating to 400°C HCH results in fusion processes followed by evaporation, and investigating in the oven, the reduction in HCH concentration present in the contaminated soil depends on the temperature and length of heating. Gaseous emissions detected were from isomers of HCH, chlorine derivatives and benzene compounds. The laboratory tests show that parameters such as temperature, heating time and air flow can influence the thermal decontamination process of the subsoil.
Keywords: Hexachlorocyclohexane; Pollution; Soils; Thermal analysis; Thermal decontamination